Pengaruh Rasio Keuangan Terhadap Laba Perusahaan Pada Perusahaan Sektor Pertanian di Bursa Efek Indonesia - Lili Sarce Joi Sapari; Yanti Marlina Timisela; Adenfi Ina Dari Doko (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine the effect of financial ratios on changes in profits in companies listed on the Indonesia Stock Exchange (IDX) in the agricultural sub-sector for the period 2020-2024. With a total of 15 companies, the sample collection technique uses purposive sampling. The research analysis technique uses multiple linear regression. The results of the study obtained by the determination coefficient test were 0.289 or 28.9%, which means that changes in profit (Y) are influenced by variable X1 (Current ratio or current ratio), variable X2 (debt to total asset ratio), variable X3 (net profit margin) together by 28.9%. The remaining 71.1% is influenced by other factors not examined in this study. Meanwhile, the influence of financial ratios on changes in profits in companies listed on the Indonesian Stock Exchange in the agricultural sub-sector can be concluded that the results of hypothesis 1 Current ratio does not affect changes in profits, while hypothesis 2 and hypothesis 3 show that Debt total asset ratio and net profit margin have a significant effect on changes in profits in agricultural sub-sector companies listed on the Indonesian Stock Exchange for the period 2020-2024.